A Photoresponsive Nanozyme for Synergistic Catalytic Therapy and Dual Phototherapy. Issue 10 (19th January 2021) - Yang, Hailong; Xu, Bolong; Li, Shanshan; Wu, Qingyuan; Lu, Mingzhu; Han, Along; Liu, Huiyu
Abstract: Dual phototherapy, including photodynamic therapy (PDT) and photothermal therapy (PTT), has shown a great prospect in cancer treatment. However, its therapeutic effect is restricted by the depth of light penetration in tissue and tumor hypoxia environment. Herein, inspired by the specific response of nanozymes to the tumor microenvironment (TME), a simple and versatile nanozyme‐mediated synergistic dual phototherapy nanoplatform (denoted as FePc/HNCSs) is constructed using hollow nitrogen‐doped carbon nanospheres (HNCSs) and iron phthalocyanine (FePc). FePc/HNCSs simultaneously exhibit peroxidase (POD)‐ and catalase (CAT)‐like activities, which not only can convert endogenous hydrogen peroxide (H2 O2 ) into highly toxic hydroxyl radicals (OH) for catalytic therapy, but also decompose H2 O2 to oxygen (O2 ) to enhance O2 ‐dependent PDT. In addition, their enzyme‐like activities are significantly enhanced under light irradiation. Combining with the excellent photothermal effect, FePc/HNCSs realize a high tumor inhibition rate of 96.3%. This strategy opens a new horizon for exploring a more powerful tumor treatment nanoplatform. Abstract : A photoresponsive nanozyme is designed for hypoxic tumor therapy. The composition of the nanostructure is not only simple but also multifunctional, which simultaneously exhibits peroxidase‐like, catalase‐like activities, photodynamic, and photothermal properties. This synergistic catalytic therapy and dual phototherapy mediated by photoresponsive nanozyme show great potential and unique advantages in tumor treatment.